2008
DOI: 10.1111/j.1525-1438.2007.01026.x
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab demonstrates activity in advanced refractory fallopian tube carcinoma

Abstract: The targeting of angiogenesis pathways in the treatment of gynecological cancers is an exciting development in cancer therapy. Bevacizumab has been shown to have activity in ovarian cancer through its inhibition of the vascular endothelial growth factor. Fallopian tube carcinoma is a rare malignancy and is often treated in a similar manner as ovarian carcinoma. We present a case of a complete response in a woman with refractory metastatic fallopian tube carcinoma treated with bevacizumab. This report demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…There was concern that withholding bevacizumab would decrease enrollment and adherence to the protocol and result in a biased survival analysis because the availability of bevacizumab postrecurrence may alter results. [12][13][14] The preliminary results from GOG-218 and the International Collaborative Ovarian Neoplasm (ICON) trial ICON-7, which evaluated the addition of bevacizumab in primary therapy of ovarian cancer, were completed at approximately the same time of opening GOG-252. 15,16 Therefore, bevacizumab was added to all arms of the current trial because it was assumed that including bevacizumab in each study regimen would not appreciably alter the relative effectiveness of the chemotherapy regimens.…”
Section: Original Reportmentioning
confidence: 99%
“…There was concern that withholding bevacizumab would decrease enrollment and adherence to the protocol and result in a biased survival analysis because the availability of bevacizumab postrecurrence may alter results. [12][13][14] The preliminary results from GOG-218 and the International Collaborative Ovarian Neoplasm (ICON) trial ICON-7, which evaluated the addition of bevacizumab in primary therapy of ovarian cancer, were completed at approximately the same time of opening GOG-252. 15,16 Therefore, bevacizumab was added to all arms of the current trial because it was assumed that including bevacizumab in each study regimen would not appreciably alter the relative effectiveness of the chemotherapy regimens.…”
Section: Original Reportmentioning
confidence: 99%
“…It was reported that VEGF receptors, R1 and R2, constitutively active on CLL cells are able to upregulate Mcl-1 and XIAP expression and leads to inhibition of apoptosis induction [66]. Interestingly, the results of the other report confirmed that VEGF and IL-6 stimulates Mcl-1 gene expression in solid tumors and lymphoproliferative malignances [69][70][71]. The inhibition of VEGF receptor ligation by kinase blockers or antibodies directed to VEGF, decreases VEGF receptor activation and p-STAT-3 (Ser727) phosphorylation.…”
Section: Bevacizumab (Rhumab Vegf Lm609 Avastin)mentioning
confidence: 90%
“…VEGF ligation to their receptors influences on phosphorylated STAT-3 perinuclear translocation by receptor-mediated endocytosis. nonsmall cell lung, breast cancer) suggested that this agent would be applicable for the treatment of any tumor which facilitates vasculature growth as being critical to cancer metastasis [70]. The strong correlation between VEGF and Mcl-1 mRNA expression in CLL was signalized [67,68].…”
Section: Bevacizumab (Rhumab Vegf Lm609 Avastin)mentioning
confidence: 99%
“…An earlier, smaller retrospective study of bevacizumab combination therapy in six patients with heavily pretreated, recurrent cervical cancer found there to be a clinical benefit in 67% of the subjects, including one complete response, one partial response, and two patients with stable disease [19]. There is also a case report of a complete response in a woman with refractory metastatic fallopian tube carcinoma treated with bevacizumab [20]. In general, bevacizumab has been well tolerated by patients.…”
Section: Angiogenesis and Cancermentioning
confidence: 94%